L’intermède guadeloupéen de Georges Rohner : l’ensemble de la mairie de Basse-Terre (1934-1936) - Marie-Emmanuelle Desmoulins (In Situ, 2005)
Still an unknown painter, Rohner did his military service in Guadeloupe where he was commissioned by the town of Basse-Terre to execute a major work of six paintings destined to decorate the council chamber of the town hall and celebrating the three hundredth anniversary of the attachment of the French West Indies to France.